Liquid Organic Fertilizer Test and Tuber Cutting on Shallots (Allium Ascalonicum L.) Growth and Yield - Bahri, Saiful; Siswadi; Purnomo, Dwijo Agus (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
This research aims to analyze the effect of liquid organic fertilizer concentration and bulbs cutting on the growth and the yield of shallots (allium ascalonicum. L). This research was conducted on december 02, 2021 until february 13, 2022 located in a garden plant food and horticulture tohudan, Tanon Lor, Gedongan, Colomadu, Karanganyar, Central Java, with an altitude of 105 m above see level. This research is Complete Random Blok Design (CRBD) factorials. The result showed that cutting tubers (P1) 0,25 a part on the parameters of observation of leaves, number of leaves, the wet weight of biomass, dry weight of biomass, number of tubers planted, number of tubers plot, tuber weight planted showed an increase with increasing LOF, while tuber weight a plot showed a decrease with increasing LOF concentration. The cutting of tubers (P2) 0,33 a part on the parameters of observation of number of leaves, the wet weight of biomass, dry weight of biomass, number of tubers planted, tuber weight planted showed an increase with increasing LOF, while the long narrow leaves, number of tubers plot, tuber weight a plot showed a decrease with increasing LOF concentration. The cutting of tubers (P3) 0,5 a part on the parameters of observation number of tubers planted, number of tubers plot showed an increase with increasing LOF, while the long narrow leaves, of number of leaves, the wet weight of biomass, dry weight of biomass, tuber weight planted, tuber weight a plot showed a decrease with increasing LOF concentration.